Economic impacts of changing technologies on New Zealand homecare delivery. Issue 3 (16th September 2019) - Hennessy, Julia Lesley; Rodrigues, Averyl
Abstract : Purpose: The population of New Zealand (NZ) is ageing; the proportion of people aged 65 and over as compared with the younger age groups is expected to increase from 15 per cent in 2016 to approximately 30 per cent by 2068. This change in demographics is bound to apply some pressure on economic resources due to factors such as superannuation and increased healthcare needs. The purpose of this paper is to explore the use of technology as being economically beneficial for managing the grey tsunami that has commenced in NZ. Though technology is still not being utilised to its full capacity in the healthcare sector, there is a reason enough to believe that it could be used in assisting with ageing in place. However, its cost-effectiveness has not been clearly demonstrated. Design/methodology/approach: A literature search was performed using search engines such as ProQuest, EBSCO, CINAHL and Google Scholar. Keywords used were ageing in place, technology, assisted living technology, ageing, telecare and telehealth. The papers selected were publicly available. To determine if the cost evaluation literature were of acceptable quality, they were assessed according to a well-recognised economic evaluation checklist by Drummond et al . (2005). Findings: As is evident from the demographic figures, there needs to be timely intervention to appropriately manage the ageing population given the projected financial and population figures. Technology has proved beneficial especially with positive ageing. A significant reason for it hardly being used is the lack of thorough studies that demonstrate its cost-effectiveness. The studies that have tackled the subject of economic evaluation have provided mixed results with some labelling technology as cost-effective and the others opposing this finding. Studies have shown that even the simplest form of technology such as a phone call, mobile health application or a pedometer can be effective. Research limitations/implications: The majority of research and funding is directed towards supporting the frail adults instead there should be equal focus on those who are reaching the old age group. Since current data suggest that people are living longer, early intervention is beneficial to reduce the number of years lived with disabilities along with associated costs of disease burden. Practical implications: Healthcare policymakers need to take more proactive steps through incorporating technology rather than deferring its use until proven beneficial by large studies as this is not feasible given the rate at which technology is developing. Studies have shown that even the simplest form of technology such as a phone call, mobile health application or a pedometer can be effective. Social implications: Technology increases awareness and allows people to be more disciplined with their health plan which increases good health. Early intervention also means relying and involving the primary level of care to manage the disease which would be more economically beneficial than postponing care until the disease progresses in which case secondary or tertiary levels of care must be sought. Originality/value: This is an emerging field in the area of aged care and only begins to expand potential horizons. Studies show that a significant number of the population prefer to stay in their own homes as they age and that with the improvement in technology this could become a reality. However, health planners need to be considering technology when developing health and social services.